2009
DOI: 10.1902/jop.2009.090138
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Inducible and Endothelial Forms of Nitric Oxide Synthase in Cyclosporin A‐Induced Gingival Overgrowth

Abstract: CsA differentially upregulated iNOS, but not eNOS, in overgrown gingiva, which may play a pivotal role in the pathogenesis of CsA-induced GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Nitric oxide (NO) is a cellular signaling molecule with vasodilatory function, synthesized in the endothelium by enzymatic activity of nitric oxide synthase (NOS), sometimes promoted by the endothelin-specific receptor [ 80 ]. Occasionally NO is also produced in the inflammatory environment by an inducible form of nitric oxide synthase (iNOS) from resident inflammatory cells [ 81 ]. Moreover, the LPS and other specific cytokines such as IL-1, TNF-α, and interferon-γ may increase iNOS synthesis [ 71 , 72 ].…”
Section: Cellular and Molecular Biology Of Gingival Overgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) is a cellular signaling molecule with vasodilatory function, synthesized in the endothelium by enzymatic activity of nitric oxide synthase (NOS), sometimes promoted by the endothelin-specific receptor [ 80 ]. Occasionally NO is also produced in the inflammatory environment by an inducible form of nitric oxide synthase (iNOS) from resident inflammatory cells [ 81 ]. Moreover, the LPS and other specific cytokines such as IL-1, TNF-α, and interferon-γ may increase iNOS synthesis [ 71 , 72 ].…”
Section: Cellular and Molecular Biology Of Gingival Overgrowthmentioning
confidence: 99%
“…Moreover, the LPS and other specific cytokines such as IL-1, TNF-α, and interferon-γ may increase iNOS synthesis [ 71 , 72 ]. Some authors have reported that iNOS is highly expressed in epithelium and connective tissues in gingivitis, and up-regulated in cyclosporine-induced GO with regard to healthy gum [ 81 ]. It has been observed that the vascular endothelium responds to reactive oxygen species (ROS) arising from oxidative stress, which appears in metabolic situations of imbalance between ROS and cellular antioxidant defense mechanisms, thus increasing iNOS activity [ 82 ].…”
Section: Cellular and Molecular Biology Of Gingival Overgrowthmentioning
confidence: 99%
“…5,6,38 Despite known roles of oxidative stress in gingival inflammation [39][40][41] and in initiation and progression of fibrotic diseases, 16,17 only some clinical studies investigate levels of OSM in GCF or plasma samples of patients receiving immunosuppressive therapy. 18,42 In a recent in vitro study, CsA at concentrations >0.1 mg/mL was shown to increase activity of glutathione peroxidase, whereas glutathione reductase activity and level of reduced glutathione were diminished in cultured oral epithelial cells. 20 Other recent studies have shown that CsA upregulates intracellular ROS generation 19 and induces oxidative stress that is suggested to play a role in the pathology of CsA-induced GO.…”
Section: Discussionmentioning
confidence: 99%
“…CsA‐induced GO has been shown to arise from altered collagen homeostasis; differences in balance between cell proliferation and apoptosis; and presence of inflammatory changes in gingival tissues 5 , 6 , 38 . Despite known roles of oxidative stress in gingival inflammation 39–41 and in initiation and progression of fibrotic diseases, 16 , 17 only some clinical studies investigate levels of OSM in GCF or plasma samples of patients receiving immunosuppressive therapy 18 , 42 . In a recent in vitro study, CsA at concentrations >0.1 μg/mL was shown to increase activity of glutathione peroxidase, whereas glutathione reductase activity and level of reduced glutathione were diminished in cultured oral epithelial cells 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between GO and various molecules, including fibrogenic IL‐6, has long been the point of interest 11,22‐25,31‐37 . IL‐6 has been linked to fibrotic tissue alterations, including pulmonary and gingival tissues, as a key cytokine 13,22,24 .…”
Section: Discussionmentioning
confidence: 99%